EXPLORATIVE STUDY OF CATALYST FOR THE AQUATIC REDOX SYSTEM GLUCOSE â SORBITOL ETHANOL - ACETALDEHYDE - Dwi Nater, Priskila
Nowadays, sorbitol is produced through hydrogenation of starch in the presence of a nickel-based catalyst at a pressure of 35-138 barg and temperature of 130°C-180°C. Acetaldehyde is produced through dehydrogenation of ethanol in the presence of a silverbased catalyst at 20 bar and temperature 140°C-170°C. The process above, operate using highly cost catalyst and conduct in high operating condition. We develop an aquatic redox reaction of glucose-ethanol sorbitol-acetaldehyde. This reaction will produce sorbitol and acetaldehyde subsequently as expected. By thermodynamics concept, it is possible for this reaction to be conducted in the presence of a catalyst. The goal of this research is to propose a catalyst with Zn as the active metal because of its selectivity as reductant. The catalyst will be modified to the form of Zn(x)Cr(y)(HCOO)(z) using Cr : Zn mole ratio of 0; 0,33; 0,5; and 1. The precursors are Zn(HCOO)2 and Cr(HCOO)3. Aqueous phase catalyst is made from stoichiometry reaction of the precursor and solid phase catalyst following the same step with the addition of NaOH. The operating conditions are equilibrium reaction (T=45°C) followed by separations (T=80°C) at ambient to separate acetaldehyde which bound to another aldehyde compound produced from glucose decomposition. Our research shows that a solid phase catalyst with Cr : Zn 0 : 1 [Zn5(OH)6(HCOO)4] has the highest performance. The feasibility study of this catalyst evidence that it’s only capable to undergo one-stage reaction, where at the next stage there is a reduction on acetaldehyde and sorbitol yield. Our catalyst also shows high performance to produce acetaldehyde more than sorbitol. For the enhancement of the research, it needed an advanced method to determine the real composition of the catalyst and also the identification of aldehyde compound which is produced from glucose decomposition and a method to determine acetaldehyde specifically.